Epidemiological aspects of enterovirus infection in the Russian Federation during the period of 2018–2019 - N. I. Romanenkova; N. R. Rozaeva; M. A. Bichurina; O. I. Kanaeva; I. G. Chkhyndzheriya; L. V. Shishkina; A. G. Madoyan; N. V. Valdaitseva (Журнал инфектологии)
Aim: Analysis of enterovirus infection morbidity and characteristics of the etiological agents of this infection on some territories of Russia in 2017.Materials and methods: We investigated 7858 samples of the biological material from the patients suffering from enterovirus infection. The isolation and identification of enteroviruses were conducted by virological and molecular methods.Results: The epidemic process and the clinical picture of enterovirus infection on different territories had some peculiarities. On some territories enterovirus meningitis was the predominant form of infection, on other territories enterovirus infection with exanthema prevailed. In Saint-Petersburg, Archangel and Saratov regions the percentage of enterovirus infection cases with the clinical picture of enterovirus meningitis was significantly higher than the percentage of enterovirus infection with exanthema. In the Komi Republic, Leningrad and Murmansk regions the percentage of infection with exanthema was statistically higher than the enterovirus meningitis portion. Enteroviruses of 30 serotypes were detected in the samples of patients suffering from enterovirus infection. We determined the etiology of sporadic and epidemic cases of enterovirus infection represented by different clinical forms. On some territories the epidemic foci of enterovirus infection among children were revealed. The etiological agents of enterovirus meningitis foci in Saint-Petersburg, Murmansk and Saratov regions were Coxsackievirus B5, Coxsackievirus B4 and Echovirus 30. The foci of enterovirus infection with exanthema in Archangel, Leningrad, Murmansk and Novgorod regions were caused by Coxsackieviruses A10, A16 and A6.Conclusion: The clinical forms of enterovirus infection on some territories were provoked by enteroviruses which dominated in the circulation on one or other territory. Enteroviruses of species B, mainly Echovirus 30, Echovirus 6 and Coxsackieviruses B1–6 were the etiological agents of enterovirus meningitis. The etiological factors of enterovirus infection with exanthema were Enteroviruses of species A, mainly Coxsackieviruses of different serotypes as well as Enterovirus 71.